PENGARUH MOTIF PENGGUNAAN MEDIA SOSIAL INSTAGRAM @SUDUTPAYAKUMBUH TERHADAP KEPUASAAN FOLLOWERS DALAM MEMPEROLEH INFORMASI DI KOTA PAYAKUMBUH - Oktavia Depinta; Anuar Rasyid (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2019)
Instagram is a social media that can upload photos and videos through the internet and information can be accessed quickly by other people en masse. Lots of content presented by Instagram users such as sharing important information about an area, this is used by some young people of Payakumbuh using the Instagram account @sudutpayakumbuh as a medium for sharing information about Payakumbuh City. This Instagram @sudutpayakumbuh account has 76.90 thousand followers. This study aims to see how much influence the @sudutpayakumbuh Instagram account has on the satisfaction of followers in getting information in Payakumbuh.This research uses a quantitative method with an explanatory approach. Data collection techniques using questionnaires distributed through links to 100 respondents and techniques to determine samples using simple ramdom sampling. And the data can be processed using SPSS 2.0.In this study, tcount 11,247 is greater than ttable, which is equal to 1,664, with a significance level of 0,000 smaller than α = 0.05, so it can be stated that the variable X has an effect on the Y variable, so it can be stated that there is an influence on the use of instagram account @sudutpayakumbuh towards the authority of followers in obtaining information in the City of Payakumbuh. The coefficient of determination (R2) obtained was 0.751 and the coefficient of determination (Rsquare) was 0.563 as a result of squaring the correlation coefficient of 0.751 x 0.751. This figure shows that the influence of the motive of using Instagram account @sudutpayakumbuh to the authority of followers in obtaining information by 56% with a medium category.